Reproductive Health and Cancer in Adolescents and Young Adults - Quinn, Gwendolyn P.; Vadaparampil, Susan T. (Advances in Experimental Medicine and Biology, 2012)
Reproductive medicine is a growing field with new technology emerging faster than we can assess consumer's perceptions of -the number of cancer survivors are growing and there is a great need to attend to their quality of life-this book addresses the needs of males and females, identifies effective communication strategies and proactive measures for health care professionals and researchers to use as well as identifying gaps in the literature where more research is needed.